On one theorem of G. Freud - Dadashova, I. B.; Mamedkhanov, J. I. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain a generalization and improvement of the G. Freud theorem on arbitrary Jordan curves in the complex plane.